PERANAN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN LEMBAGA DAN PENINGKATAN MOTIVASI GURU SEKOLAH PENGGERAK - Holdi, Muhammad; Mulyono, Sugeng; Gunadi, Gunadi; Sulaiman, Sulaiman (Universitas Hamzanwadi, 2023)
The objectives of this research are: i) To explore and describe the role of school principals in developing institutions and increasing the motivation of driving school teachers in East Lombok Regency. ii) To explore and describe the challenges and opportunities for school principals in developing institutions and increasing the motivation of driving school teachers in East Lombok Regency. ii). This research is a type of field research with a descriptive quantitative approach. The population in this study was 324 people consisting of 24 school principals and 300 teachers in elementary school education units. The sample in this study were 10 elementary school principals and 22 teachers who ran the Driving School Program in East Lombok Regency. The data analysis technique used in this research is the percentage technique. The research results show that; (i) The leadership role of school principals in developing institutions at driving schools in East Lombok Regency is at 85,0%. and entered the